Abnormal connection between the posterior insula and the gastric network among patients with functional constipation - Zha, Dehua; Chen, Jiajing; Yang, Yanyan; Zhang, Liang; Tao, Shaohua; Wang, Wei; Li, Ming (Frontiers in Human Neuroscience, 2025)
BackgroundFunctional constipation (FCon) is frequently accompanied by psychological disorders, implicating the interaction between the gastrointestinal symptom and brain dysfunction in FCon. Recent studies combining electrogastrogram and resting-state functional magnetic resonance imaging (fMRI) have reported a novel gastric network. Besides, the fMRI activity of the gastric network was also coupled with the insular fMRI signal. However, little is known about the connection between the gastric network and the insula in FCon.MethodsBased on rs-fMRI, functional connectivity (FC) using a large sample of 652 healthy subjects identified the insular cortex as the most closely linked to the gastric network. Then, seed-based FC and dynamic functional connectivity of the gastric network and the gastric-related insular cortex were calculated and compared in 35 patients with FCon and 36 healthy controls. Constipation symptoms were measured using the Patient Assessment of Constipation Symptom Scale (PAC-SYM) and the Wexner Constipation Scale. Their relationships with alterations in the gastric network-insula subregion were investigated.ResultsThe posterior insular cortex presented a strong connection with the gastric network with large-scale resting-state fMRI data sets of healthy participants. FCon patients had significantly decreased FC (t = −2.19, p = 0.032) in the left posterior insula and gastric network compared to healthy controls and were significantly negatively correlated with PAC-SYM (r = −0.407, p = 0.015) and Wexner Constipation Scale (r = −0.483, p = 0.003) scores.ConclusionThe abnormality of the connection between the posterior insula and the gastric network may be the prominent neuroimaging feature on FCon, which sheds light on a new perspective on the pathophysiology of FCon.